Short-Term Sedimentation Dynamics of Temperate Mangroves in Western Port Bay, Victoria - Sayers, Sabrina; Reef, Ruth (Frontiers in Marine Science, 2022)
The promotion of sedimentation by mangrove ecosystems with adequate sediment supply has been well documented. However, predicting the amount of accretion or erosion at a specific point, is difficult due to the inherent stochasticity of sediment movement and deposition. Forcings which have been thought to influence short-term sedimentation rates, such as the amount of suspended matter in the incoming water, the wave regime at the site, elevation above sea level, distance from the low tide mark, and vegetation density, were investigated using large arrays of erosion pins at five sites around Western Port, Victoria over the course of one and a half years. We analysed large scale/short-term and small-scale/longer-term vertical displacement within and between sites, and quantified small-scale intra-site variability. Results show, that while all study sites within Western Port were accreting sediment, they were not doing so at the same rate, and both intra-site and inter-site variability is high. Short-term large-scale or site wide analysis shows that total suspended matter and significant wave height did not significantly affect vertical displacement rates. Surprisingly, neither distance from water nor vegetation density significantly affected vertical displacement or explain the spatial distribution of accretion and erosion within the sites. The coefficient of variation at each pin shows that there is high temporal variability in vertical displacement at each location, with individual pins alternating between erosion and accretion over time. Our study finds that while large scale (1 km2) patterns of sedimentation are temporally consistent, small scale patterns (<100 m2) are difficult to predict. This small-scale stochasticity therefore compounds management of mangrove ecosystems, especially as it relates to predicting the response to sea level rise. Thus, investment in small scale management of vegetation density, or microtopography, is perhaps not required for overall shoreline stability with sea level rise and blue carbon accumulation, making ecosystem restoration more feasible where resources are limited. However, at larger, forest-wide, spatial scales a higher level of predictability exists such as the overall response of the coastal tract to prevalent wave energy and sediment supply.